2006
DOI: 10.1111/j.1468-0289.2006.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

The causes and consequences of rent‐seeking in Northern Ireland, 1945–721

Abstract: SUMMARY Northern Ireland’s economic performance during the ‘golden age’ was weak. Crafts suggested that rent‐seeking was an important determinant of this poor record. This article offers support for such a conclusion. It is suggested that the growth record was shaped by British regulations preventing conflicts of ministerial interest not being made operational until 1963. This institutional divergence tended to promote rent‐seeking behaviour, which impeded the pursuit of an industrial policy that could promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This emphasis on contingency within the institutional geography approach finds corroboration in the 'laboratory' of the 'Stormont' regime (c1921-1972 as well as more contemporary 'laboratory' of asymmetric devolution in the UK. The argument of Rodríguez-Pose and Gill finds application in explaining the causes and consequences of rent-seeking in Northern Ireland (NI) (Crafts, 1995;Brownlow, 2007).8 These empirical studies suggest that between 1945 and 1963 the institutional geography of the DA was associated with cronyism, rent-seeking, devolution and this resulted in slow regional economic growth.9 A number of economists, writing from a variety of perspectives, have considered the specific financial and economic failings of the Stormont settlement (Rowthorn, 1981;Gibson, 1996). As a result the institutional-economic nexus has been explained as contributing to the region's economic failings (Gibson, 1996;Heald, 2003).…”
Section: Institutional Geography and 'Economic Dividends'mentioning
confidence: 99%
See 2 more Smart Citations
“…This emphasis on contingency within the institutional geography approach finds corroboration in the 'laboratory' of the 'Stormont' regime (c1921-1972 as well as more contemporary 'laboratory' of asymmetric devolution in the UK. The argument of Rodríguez-Pose and Gill finds application in explaining the causes and consequences of rent-seeking in Northern Ireland (NI) (Crafts, 1995;Brownlow, 2007).8 These empirical studies suggest that between 1945 and 1963 the institutional geography of the DA was associated with cronyism, rent-seeking, devolution and this resulted in slow regional economic growth.9 A number of economists, writing from a variety of perspectives, have considered the specific financial and economic failings of the Stormont settlement (Rowthorn, 1981;Gibson, 1996). As a result the institutional-economic nexus has been explained as contributing to the region's economic failings (Gibson, 1996;Heald, 2003).…”
Section: Institutional Geography and 'Economic Dividends'mentioning
confidence: 99%
“…Rodríguez-Pose and Gill argue that the impact can be damaging to national efficiency as competitive bidding for FDI flows leads to a deadweight loss at the aggregate level (Rodríguez-Pose and Gill, 2005). 8 Brownlow found that the absence of conflict of interest regulations that existed under the devolved settlement -when combined with the strong overlap between business and political elites -tended to promote rent-seeking (Brownlow, 2007). 9 Lawrence viewed the potential accessibility of political actors within NI as a strength of the Stormont settlement.…”
Section: Footnotesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, Jamison argues that Westminster, determined to replace the Polaris nuclear deterrent, consistently advertised and exaggerated the programme's employment opportunities in Scotland. Brownlow suggests that links between those awarding government grants in N. Ireland and those receiving them, coupled with the lack of an industrial policy seeking to move resources from declining to new industries, were significant contributors to the province's poor economic performance in the golden age. Finally, Foster considers the forces and events behind dramatic and unforeseen recent change since the 1970s in the Republic of Ireland's politics, economics, cultural influences, religious profession, and gender roles.…”
Section: (Vi) Since 1945
Hugh Pemberton
University Of Bristolmentioning
confidence: 99%
“…The observations of both Kornai and more recent authors have particular resonance in the DMCL case. A number of authors have demonstrated that rent-seeking, as induced by poor institutional design related to socio-political inequalities, contributed to weakening the supply-side of region's economy prior to the outbreak of the Troubles (Crafts, 1995;Brownlow, 2007). As we will see in the next section, violence would further compound underlying economic weaknesses.…”
Section: Industrial Policy and The Sbc Approachmentioning
confidence: 99%